HISTORY OF THE ORIGIN, EQUIPMENT AND TECHNIQUE OF TABLE TENNIS (Eureka Journal of Physical and Chemical Research, 2026)
This article analyzes in detail the history of the origin of table tennis, the stages of its formation and the level of its development today. Initially appearing in England at the end of the 19th century as an indoor alternative to the game of tennis, table tennis gradually developed from a simple recreational activity to an international professional sport. The article also provides information about the initial equipment of the game, the origin of the term "ping-pong" and the processes of its commercialization. It also analyzes the establishment of a unified set of rules for table tennis through the establishment of the International Table Tennis Federation (ITTF), the holding of world championships and the global popularization of the sport as an important historical milestone.
Keywords: Table tennis, ping-pong, history of table tennis, origin of the sport, international sports organizations, International Table Tennis Federation, Olympic Games, Seoul 1988 Summer Olympics, evolution of sports equipment, development of rackets and balls, rules of the game, world championships, sports and healthy lifestyle, physical development, reflexes and agility, sports strategy.